Flood mitigation in urban areas: Adopting governance approach - Sajida; Sekar Arum Nuswantari; Ahmad Luthfi (Center for Science and Technology, IAIN Surakarta, 2023)
Even though flood disasters are becoming more frequent on an annual basis, this category of disaster is still one of the problems that has not shown any significant signs of progress toward a better direction. In the meantime, a number of studies have arrived at the conclusion that an appropriate policy approach can reduce the severity of disasters of this kind. We are making an effort to gain an understanding of the degree to which the policy direction of the government is moving toward flood management, particularly in urban areas. In order to accomplish this, we are examining a wide range of written materials and documents that are connected to the administration of flood control in Indonesia. Our review, which examines the implementation of the most recent flood mitigation, leads us to make recommendations regarding how flood management can take a governance approach to the process of flood mitigation. These recommendations will be based on the findings of our review. In order to lessen the likelihood of flooding, the government will need to lay a solid foundation from both strategic and tactic perspective.